Digital Transformation and Survival Strategies MSMEs during the Pandemic: Evidence East Java Indonesia - Sri Anugrah Natalina; Binti Mutafarida (Mahameru Publisher, 2023)
As a form of digital transformation for businesses that can survive for MSMEs during this pandemic, MSMEs in East Java are considered to also adapt to this digital transformation. The concept of the National Economic Recovery is that the government provides support incentives for MSMEs to be able to survive during the pandemic. This study will be researched and discussed using qualitative descriptive methods. The samples in this study used purposive sampling techniques with a total of 100 respondents, which matched the criteria in the study. Respondent criteria are MSME actors who have existed before the pandemic and continue to survive during the pandemic. This success shows that the majority of MSMEs in East Java has implemented a survival strategy for the industrial landscape so that it shows growth. The growth of MSMEs is derived from the concept of adaptability of this survival strategy and the implementation of the National Economic Recovery so that there is a stimulus from the government for MSMEs.